Proceedings of the Symposium on Algebraic Heometry in East Asia (World Scientific, 2002)
This book is the proceedings of the conference "Algebraic Geometry in East Asia" which was held in International Institute for Advanced Studies (IIAS) during August 3 to August 10, 2001. As the breadth of the topics covered in this proceedings demonstrate, the conference was indeed successful in assembling a wide spectrum of East Asian mathematicians, and gave them a welcome chance to discuss current state of algebraic geometry.